Implantação de um modelo de pré-natal coletivo na assistência às gestantes no setor privado - FONTES, ROSANA SELERI (2018)
Prenatal care is characterized as an important instrument to identify risk factors, to perform timely interventions to reduce maternal, fetal, neonatal and infantile morbidity. It also has a psychological and social purpose, representing a way of rescuing bodily perception, self-care, the effective participation of women in prenatal and childbirth, and the culture of normal childbirth, which has been lost in today's society. For all objectives to be achieved, the compo-sition of the assistance team is required to be multidisciplinary. It is not yet scientifically prov-en the effectiveness of current prenatal programs and many models are proposed. Among them, the group prenatal care, described in the early 90s by an midwife, and pioneer in the USA, with more than 500 groups currently in the country. Through a descriptive study, this research was been developed to implement and describe a multiprofessional group pre-natal care program, carried out in the private health system, in the region of Vale do Paraíba-SP, Brazil, based on the proposals of the Centering Healthcare Institute (US), showing the results obtained in conjunction with a holistic and humanized care for the pregnant woman. One hundred and sixty pregnant women were served in prenatal care and childbirth assistance, with 52 group prenatal meetings taking place from August 2016 to December 2017. The women attended 2 to 7 meetings each, with 2 hour-duration, where participated obstetrician doctor, pediatrician doctor, midwives, psychologists, nutritionist and physiotherapist. The results showed low prematurity rates (5.6%), normal pregnancy weight gain (10,5kg), high rates of normal childbirth (72.5%), high levels of healthy perineum or mild perineal lesions in childbirth (74.1%), shorter average time of labor (8.45 hours), minor neonatal complications (1.9% of ICU hospitalization), high Apgar scores in the first minute (96.8%). Among the newborns, 11,5% of them were low weight for gestational age. The pregnant women of the group were more likely to contact Doulas to accompany the labor (75.6%). The participants and the professionals involved reported satisfaction with the model, as reports described in the study.